Tumor Markers in Pancreatic Cystic Fluids for Diagnosis of Malignant Cysts. Issue 3 (July 2017) - Levy, Alexandre; Popovici, Theodora; Bories, Phuong-Nhi
Background and aim: Early diagnosis of premalignant or malignant pancreatic cysts is essential to improve prognosis. Sampling of pancreatic cyst fluid by fine-needle aspiration during endoscopic ultrasonography (EUS) enables cytopathological examination combined with biochemical analysis. This study aimed to provide an aid based on biological markers for the preoperative management of patients with pancreatic cysts. Methods: Pancreatic fluids obtained by EUS-guided fine-needle aspiration from 115 patients with cystic lesions were assayed for amylase, lipase, carcinoembryonic antigen (CEA), CA 19-9 and CA 72-4. In addition, chromogranin A (CgA) and neuron-specific enolase (NSE) were measured in 28 fluid samples. Results: ROC curve analysis of the different markers for diagnosis of mucinous cysts showed that CEA had the highest area under the curve (0.93, 95% CI 0.87-0.97), with a sensitivity and specificity of 89% and 93%, respectively, at the cutoff value of 317 μg/L. The CgA and NSE concentrations in 5 NET cysts (median values of 210 [63-492] and 68.5 [9-496] μg/L, respectively) were higher than in 23 other cysts (median values of 8 [7-828] and 2.7 [0.5-35.8] μg/L, respectively) (p = 0.0015 and p = 0.0045, respectively). Conclusions: CEA is the best marker for identifying a cyst as mucinous. In case of low levels of CEA, our results suggest that CgA and NSE measurements may be helpful in the diagnosis of a neuroendocrine tumor and therefore deserve further investigation.